Reward vs. Retaliation—the Role of the Mesocorticolimbic Salience Network in Human Reactive Aggression - Gan, Gabriela; Preston-Campbell, Rebecca N.; Moeller, Scott J.; Steinberg, Joel L.; Lane, Scott D.; Maloney, Thomas; Parvaz, Muhammad A.; Goldstein, Rita Z.; Alia-Klein, Nelly (Frontiers in Behavioral Neuroscience, 2016)
The propensity for reactive aggression (RA) which occurs in response to provocation has been linked to hyperresponsivity of the mesocorticolimbic reward network in healthy adults. Here, we aim to elucidate the role of the mesocorticolimbic network in clinically significant RA for two competing motivated behaviors, reward-seeking versus retaliation. 18 male participants performed a variant of the Point-Subtraction Aggression Paradigm (PSAP) during functional magnetic resonance imaging (fMRI). We examined whether RA participants compared with non-aggressive controls would choose to obtain a monetary reward over the opportunity to retaliate against a fictitious opponent, who provoked the participant by randomly stealing money from his earnings. Across all fMRI-PSAP runs, RA individuals vs. controls chose to work harder to earn money but not to retaliate. When engaging in such reward-seeking behavior vs. retaliation in a single fMRI-PSAP run, RA individuals exhibited increased activation in the insular-striatal part of the mesocorticolimbic salience network, and decreased precuneus and ventromedial prefrontal cortex activation compared to controls. Enhanced overall reward-seeking behavior along with an up-regulation of the mesocorticolimbic salience network and a down-regulation of the default-mode network in RA individuals indicate that RA individuals are willing to work more for monetary reward than for retaliation when presented with a choice. Our findings may suggest that the use of positive reinforcement might represent an efficacious intervention approach for the potential reduction of retaliatory behavior in clinically significant RA.